2022
DOI: 10.20944/preprints202209.0097.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sacred Groves and Natural Sites Conservation for Tourism in Local Communities in Nigeria

Abstract: The purpose of this study is to examine the potential of the sacred groves and natural sites for tourism in local communities in Nigeria. Three communities in Inyi town were chosen as case studies: Umuome, Enugwu-Inyi, and Alum, using a purposive sampling technique. An ethnographic data collection method was adopted, using in-depth interviews and direct observation. Grove locations were located and mapped using a geographic information system (GIS) throughout the research area. The secondary data was obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The study focuses on monolithic sites in Cross River State, distributed among the six main clans in the Ikom Local Government Area (Ejikeme et al, 2020;Ejikeme, 2020Ejikeme, , 2016. These include Nta, Nselle, Abanjom, Nde, Ekajuk and Nnam.…”
Section: The Study Of the Areamentioning
confidence: 99%
See 3 more Smart Citations
“…The study focuses on monolithic sites in Cross River State, distributed among the six main clans in the Ikom Local Government Area (Ejikeme et al, 2020;Ejikeme, 2020Ejikeme, , 2016. These include Nta, Nselle, Abanjom, Nde, Ekajuk and Nnam.…”
Section: The Study Of the Areamentioning
confidence: 99%
“…The ten monolith sites investigated were Alok, Emaghabe, Nlun, Ntolshi, Edankono, Agba, Nkirigom, Ntol, Njemitop, and Nebrokpa. The monoliths are called according to the names of the communities (Ejikeme, 2016).…”
Section: The Study Of the Areamentioning
confidence: 99%
See 2 more Smart Citations
“…This religious and socio-cultural practice has enabled sacred groves to harbour a rich biodiversity of flora and fauna and has played a significant role in the conservation of biodiversity . Ejikeme and Okonkwo (2022) found that Sacred Groves form an attraction, both for the community and the area surrounding the community. The essence of tourists' decision in choosing a destination is of much significance in determining the best places to go that links them to the critical aspects that may influence the decision-making (Ortaleza and Mangali, 2021).…”
Section: Introductionmentioning
confidence: 99%